(untitled) (Jurnal Teknologi (Sciences & Engineering), 2015)
The aim of this study is to investigate the influence of different composition of cellulose acetate phtalate (CAP) on the membrane structural properties of polysulfone (PSf) membrane which in turn affect the separation performance of PSf/CAP blend membrane. The PSf/CAP blend membranes were prepared by using casting solutions contain 17 wt% of polymer via wet phase inversion process. The results showed that increasing the composition of CAP in PSf/CAP blend membranes increased molecular weight cut-off (MWCO), average pore size and pore density which then increased protein solution permeate fluxes but reduced proteins rejection of PSf/CAP blend membranes. Pure PSf membranehas the lowest membrane structural properties compared to blend membranes. This characteristic contributed to decrease in protein permeation flux and increase proteins rejection.Â